The Early Impacts of COVID-19 on Food Security and Livelihood in Vietnam - Aaron, Alec; Baidya, Anurima; Wang, Jun; Chan, Christabel; Wetzler, Erica; Kang, Yunhee (Frontiers in Sustainable Food Systems, 2021)
In April 2020, Vietnam initiated a country-wide lockdown to curb the spread of COVID-19. This secondary data analysis evaluates whether NGO-supported households (n = 3,431) reporting to be severely impacted by the lockdowns differ from those reporting a lesser impact, regarding food availability within households and at markets and affordability. 19.2% of respondents indicated that the pandemic had severely impacted their livelihoods. In the severely impacted group, there was a higher percentage of urban residents (25.3 vs. 8.6%; p < 0.001), households reporting decreased income (85.4 vs. 39.9%), and females (56.4 vs. 45.6%; p < 0.001) than in the less impacted group. Both groups reported similar availabilities of staple food groups at the household-level, but the availability of green vegetables was lower in the severely affected group (Adjusted OR [aOR] = 0.62, 95% CI: 0.38, 1.00) than in the less affected group. However, local market availability of hygiene items (aOR = 1.64, 95% CI: 1.13, 2.39) and essential medicines (aOR = 1.80, 95% CI: 1.29, 2.50) were higher for the more impacted group relative to the less impacted group. While the self-reported livelihood impact of COVID-19 was associated with a loss of income, the association of indicators of food availability within households and at markets, and essential item affordability, did not frequently differ. Self-determination of a severe economic impact may represent a relative change in the household's socioeconomic status from before the pandemic.